2021
DOI: 10.1177/0733464820987350
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions and Attitudes Toward Dementia in Predominantly African American Congregants

Abstract: The purpose of this study was to identify the perceptions and attitudes of African American congregants toward dementia before and after attending a dementia-focused workshop. Six churches in Metropolitan Atlanta, Georgia, hosted the workshops. Attendees ( N = 171) participated in a free association exercise to evaluate their perceptions and attitudes toward dementia. Before and after the workshop, participants wrote words and phrases that occurred to them when they thought of dementia. Content analysis was us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…The success of culturally tailored interventions is consistent with prior studies that focused on providing education on cancer, HIV, and obesity to Black/African American populations by involving the target community in intervention design and using valued cultural settings like barbershops to disseminate health knowledge 45–47 . Similarly, faith‐based interventions in Black communities have successfully disseminated dementia knowledge 14,48,49 . Therefore, when designing interventions that target racial/ethnic minority groups, it is critical to incorporate culturally tailored strategies into the study design, such as delivering the intervention in trusted community settings, limiting barriers to access and literacy requirements, offering quality content in preferred languages, and using validated instruments tailored to the language and culture of the target population.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…The success of culturally tailored interventions is consistent with prior studies that focused on providing education on cancer, HIV, and obesity to Black/African American populations by involving the target community in intervention design and using valued cultural settings like barbershops to disseminate health knowledge 45–47 . Similarly, faith‐based interventions in Black communities have successfully disseminated dementia knowledge 14,48,49 . Therefore, when designing interventions that target racial/ethnic minority groups, it is critical to incorporate culturally tailored strategies into the study design, such as delivering the intervention in trusted community settings, limiting barriers to access and literacy requirements, offering quality content in preferred languages, and using validated instruments tailored to the language and culture of the target population.…”
Section: Discussionsupporting
confidence: 58%
“…[45][46][47] Similarly, faith-based interventions in Black communities have successfully disseminated dementia knowledge. 14,48,49 Therefore, when designing interventions that target racial/ethnic minority groups, it is critical to incorporate culturally tailored strategies into the study design, such as delivering the intervention in trusted community settings, limiting barriers to access and literacy requirements, offering quality content in preferred languages, and using validated instruments tailored to the language and culture of the target population.…”
Section: Discussionmentioning
confidence: 99%
“…Herrmann et al reviewed dementia-related stigma studies and found that stigma might be more common among America's ethnic and immigrant minorities (Herrmann et al, 2018). Another study in the United States indicated that African Americans often use negative words and phrases to describe PLWD, such as "fear," "crazy," and "damned" (Epps et al, 2021). In Denmark, Nielsen et al compared three immigrant groups, Polish, Pakistani and Turkish, with native Danish people regarding their attitude towards dementia (Nielsen and Waldemar, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…African American families affected by dementia are often hesitant to share the dementia diagnosis with others due to fear or shame. 11 The position of African American churches leads to the church playing a vital role in establishing community norms to address the stigma of dementia and potentially increasing the quality of life for families. [12][13][14][15] In addition, African American churches play a significant role in health promotion within the African American community and church leaders desire to form partnerships with health systems to promote healthy behaviors.…”
mentioning
confidence: 99%
“…Disparities, as well as the emotional strain experienced by families faced with dementia, underscore the need to identify culturally relevant services and resources to improve the quality of life for African American caregivers and persons living with dementia (PLWDs). African American families affected by dementia are often hesitant to share the dementia diagnosis with others due to fear or shame 11. The position of African American churches leads to the church playing a vital role in establishing community norms to address the stigma of dementia and potentially increasing the quality of life for families 12–15.…”
mentioning
confidence: 99%